Pengaruh Konten TikTok, Harga, Dan Customer Experience Terhadap Keputusan Pembelian Followers TikTok Pada Warung Mekar Jaya Malang - Tyas, Roihana Ervillia Rizki Rahmaning; Rachma, N; Hardaningtyas, Ratna Tri (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to determine and analyze the effect of TikTok content, price, and customer experience on purchasing decisions for TikTok followers at Warung Mekar Jaya Malang. This research method uses quantitative methods. This study uses primary data which is processed and obtained from distributing questionnaires. The number of respondents in this study were 93 respondents. In this study using a Likert Scale and multiple linear regression analysis with the help of the Statistical Product and Service Solution (SPSS) program version 26. The results of this study indicate that the Tiktok Content, Price, and Customer Experience variables simultaneously have a significant effect on the Tiktok Followers Purchase Decision at Warung Mekar Jaya Malang. Partial results also show that the Tiktok Content, Price, and Customer Experience variables have a positive and significant effect on the Purchase Decision of Followers Tiktok at Warung Mekar Jaya Malang. Keywords: TikTok Content, Price, Customer Experience, and Purchase Decision